THE EFFECT OF COMPANY VALUE, PROFITABILITY AND LIQUIDITY ON CSR DISCLOSURE - Sandelia Sandelia; Agus Munandar (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
The objective of this research is to examine the impact of enterprise value, profitability, and liquidity of the entities on the disclosure of corporate social responsibility. Quota sampling method was chosen to determine sample data. Sample for this research is entities that have SRI-KEHATI index on Indonesia Stock Exchange with financial report years 2019-2021. This paper uses linear regression for hypothesis testing. The results are independent variable (enterprise value, profitability, and liquidity) positively effect to dependent variable (CSR Disclosure). This implies that companies with higher enterprise values, profitability, and liquidity are more inclined to disclose information about their corporate social responsibility efforts.